STRATEGI MOMENTUM DAN STRATEGI VOLATILITAS MOMENTUM PADA SAHAM INDEKS LQ 45 - Nanda Nanda (Jurnal Ilmu Manajemen, 2021)
This study looks at the return of the momentum strategy and the momentum volatility strategy of stocks listed on the LQ 45 Index for the 2010-2019 period. The method used in this research is the method of Jagedeesh and Titmant (1993) and Malin and Borhold (2011). Winning portfolios are formed by buying stocks with the best past return performance and selling stocks with past poor returns for a momentum strategy. Meanwhile, the loser portfolio is created by buying stocks with bad returns and selling stocks with good returns in the past. A momentum and volatility type is used in forming a portfolio of winners and losers for a momentum volatility strategy. Formations and observations were used 3,6 and 12 months—return momentum when the loser minus an optimistic winner. Significant momentum is determined by a one-sample t-test using SPSS 21. The study did not find returns from all momentum strategies statistically significant on stocks with LQ 45 Index for the 2010-2019 period. This result explains that the LQ 45 index is already in a weak form of efficient market condition. Investors cannot use this strategy to obtain excess returns when transacting on the LQ 45 index.